Adjudications and self-harm in prisons during COVID-19: three-year longitudinal analysis of the Offender Personality Disorder Pathway in England and Wales - Gillespie, Steven M. (BJPsych Open, 2025)
Background: The effects of pandemic-related restrictions on people in prisons who tend to have multiple complex health needs are not well understood. Aims: We aimed to measure changes in adjudications and self-harm among people in prisons before and during the pandemic. Method: We examined effects of time and demographic characteristics on odds and counts of adjudications and self-harm over a three-year period, starting one year before the COVID-19 pandemic, in 861 individuals from 21 Offender Personality Disorder Pathway prison sites. Results: The odds of adjudicating were lower in people of older age (odds ratio 0.98 (95% CI: 0.96–0.99)), and during COVID-19 year one (odds ratio 0.37 (95% CI: 0.23–0.60)) and year two (odds ratio 0.40 (95% CI: 0.25–0.65)) compared to pre-COVID-19. Being of White ethnicity was associated with increased odds (odds ratio 4.42 (95% CI: 2.06–9.47)) and being older was associated with reduced odds (odds ratio 0.97 (95% CI: 0.95–0.99)) of self-harm. The odds of self-harm were significantly reduced during COVID-19 year two (odds ratio 0.45 (95% CI: 0.26–0.78)), but not during COVID-19 year one (odds ratio 0.68 (95% CI: 0.40–1.14)), compared with the 12 months before COVID-19. Conclusions: Although adjudications and self-harm were generally lower during the pandemic, younger people showed increased odds of adjudications and self-harm compared with older people, while White people showed increased odds of self-harm compared with people of the global majority. Our findings highlight the importance of considering potential health inequities and environmental effects of lockdowns for people in prisons.